Marker validation for salt tolerance in Indica rice - SUPRAYOGI SUPRAYOGI; PRITA SARI DEWI; EKA OKTAVIANI; ALWA WIDI AISYA (Society for Indonesian Biodiversity, 2022)
Abstract. Suprayogi, Dewi PS, Oktaviani, E, Aisya AW. 2022. Marker validation for salt tolerance in Indica rice. Biodiversitas 23: 4517-4523. The development of salt-tolerantrice variety is of importance with concern to the use of the coastal area for rice production and, consequently, the development ofarapid and accurate method of variety selection. Molecular markers associated with Quantitative Trait Loci (QTL) for salt tolerance in rice have been reported elsewhere. This research aimed to identify molecular markers associated with salt tolerance in rice. The research was carried out from September 2020 to February 2021 at Plant Breeding and Biotechnology Laboratory, Faculty of Agriculture, Jenderal Soedirman University, Indonesia. Nine Simple Sequence Repeat (SSR) markers and one Sequence Tagged Site (STS) marker were evaluated for their association with salt tolerance. The rice varieties consisted of three salt-tolerant varieties, one salt-sensitive variety, and six commercial varieties. Nona Bokra PCR amplicon was used as a positive control for DNA band scoring. Binary data of the amplicon banding pattern were analyzed using Principal Component Analysis (PCA) to determine the grouping of the evaluated varieties about their tolerance to assigned markers. The result demonstrated that the evaluated rice varieties fell into four groups of marker resemblances. Among the evaluated SSR markers, RM 3412, RM 342, RM 8094, and Wn 11463 significantly contributed to the grouping. The present study confirmed that Wn 11463 is a strong marker for salt tolerance in rice. However, validation needs to be made on a broader range of genotypes to see the significance of RM 8094 and RM 3412 as salt tolerant markers.